Inferência de micrornas candidatos a influenciar a expressão do gene imunosupressor HLA-G - Porto, Iane de Oliveira Pires (2014)
MicroRNAs (miRNAs) are small non-coding RNAs involved in post-transcriptional expression regulation by inducing mRNA degradation or translation inhibition. Some miRNAs are known to regulate HLA-G expression, an important immunemodulatory molecule that inhibits both Natural Killer and cytotoxic T cells through interaction with inhibitory receptors. The HLA-G is associated with maternal-fetal tolerance, tissue acceptance in transplants and the progression of tumors. The mechanisms underlying HLA-G expression control are not completely understood, however, its 3’untranslated region (3’UTR) is reported to play an important role on gene regulation influencing mRNA stability and interacting with miRNAs such as miR-148a-3p. In this study, we performed a systematic analysis of all miRNAs that are good candidates to act as HLA-G regulators. In order to determine the miRNAs with the highest potential to influence HLA-G expression, we compared the outputs of three distinct algorithms - miRanda, RNAhybrid and Pita. For this purpose, a method of miRNA inference was developed using Perl scripts to compare and filter results and a scoring system was created in order to evaluate both the binding stability of the miRNA/mRNA interaction and the miRNA specificity to its target sequence. Then, a panel of miRNAs with great potential of controlling HLA-G expression was generated.